Stigma : marking skin in the early modern world - Dauge-Roth, Katherine; Koslofsky, Craig (Perspectives on sensory history., 2023)
"Investigates the intersecting histories of tattooing, branding, stigmata, baptismal and beauty marks, and the wounds and scars borne by early modern men and women. Examines these forms of dermal marking as manifestations of a powerful and ubiquitous material practice"--